An Acrylic Latex Filled with Zinc Oxide by Miniemulsion Polymerization as a Protective Coating for Stones. Issue 11 (8th July 2014) - Serra, Chiara Letizia; Tulliani, Jean‐Marc; Sangermano, Marco
Abstract An acrylic latex filled with ZnO by miniemulsion polymerization are developed for stone protection. The main latex chemical properties are determined through dynamic light scattering and differential scanning calorimetry measurements. Contact angle determination, capillary water absorption, scanning electron microscopy observations, and colorimetric measurements are also used to evaluate the coating. The accelerated photo‐aging of the dried films are monitored by infrared spectroscopy. The synthesis of a water dispersion product and the photostability reached through the introduction of ZnO represent the main advantages of this coating for the use in the field of stone conservation.<inline-graphic xlink:href="ark:/27927/pgh2ck9dtws" content-type="mame201400074-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />